Experimental Analysis on The EFECT Of Partial Replacement of Cement By Waste Bio Product of Bauxite Residue : A Review - Mohammed Rizwan Raza; Ajay Swarup (International Journal of Scientific Research in Civil Engineering, 2021)
An increasing amount of red mud (RM) is being generated globally due to the growth in aluminium production. In general, 0.8 to 1.5 tons of RM can be generated per ton of produced alumina. With the rapid development of the aluminium industry, approximately 1.7 billion tons of RM is generated per year globally. The pH of RM is typically 10.5–12.5 owing to the hydroxide (NaOH) added during aluminium production. The case for reusing red mud is not without challenge – the toxic nature of the mud has served as a barrier to reuse. And while more research is needed, recent studies have brought to light the promising potential for red mud to be reused in a variety of applications within the construction industry. In addition to providing an outlet for mass quantity utilization of red mud, studies have found that in many cases, red mud can even offer improvements to the end product.
Keywords: Red Mud; Compressive Strength Test; Waste Material; Concrete Technology; Concrete; Physical Properties